Pemberdayaan UMKM Alat Permainan Edukatif Terdampak Pandemi di Wonorejo - Eko Sri Haryanto; Tri Prasetyo Utomo (Abdi Seni, 2023)
The Community Partnership Program "Empowerment of UMKM Empowerment of Educational Game Tools Affected by a Pandemic in Wonorejo" aims to increase the competitiveness of fostered partners in facing a wider market. The first partner for this community service activity is UKM APE Otak-atik, this UKM has a segmentation in the general public as well as book and stationery shops located in the Wonorejo area, Karanganyar Regency, Central Java. The potential for developing APE products (Educative Game Tools) is still very wide open. Limited human resource capabilities, business networks, and limitations in the number and type of equipment prevent partners from taking advantage of existing opportunities. After the assistance is given, it is hoped that the partners will be able to become more resilient craftsmen. Partners can develop the design, production, market, and selling value of products, to increase family income, then absorb more labor from the surrounding community. This community service activity was carried out for eight months. Activities carried out in the form of; equipment grants for the use of production equipment with appropriate technology, management training, and online sales training. After getting a touch of good design, good management, modernization of production equipment, promotional media, and online sales, it is expected to be able to increase the competitiveness of partners in facing the free market.